Pemanfaatan Lingkungan Alam Sebagai Sumber Belajar IPA Kelas 3 Sekolah Dasar (SD) Alam Ma’had Islam Pekalongan - Muhammad Khoiruzzadi; Nur Rahmawati Amalia (JIP Jurnal Ilmiah PGMI, 2020)
The surrounding natural environment can be an attractive learning resource for lower class students, because children at this stage need concrete learning. The purpose of this study is to find out how the process and procedure of utilizing the surrounding natural environment as a source of learning in Natural Sciences at SD Ma'had Islam Pekalongan and its supporting and inhibiting factors. This research includes field research with a qualitative descriptive approach, data taken based on interviews with principals and class 3 teachers, as well as observations of the learning process of science in class 3. The results of the research are in the procedure of utilizing the natural environment as a source of natural science learning. The first is planning with make RPP. Considerations that need to be considered in this plan are by paying attention to learning resources, learning media, and learning methods. Second, the implementation of learning begins with introduction, core activities, and closing. Third, evaluation in natural science learning with questions and answers and assignments. The supporting factors are the teacher's knowledge about learning in the natural environment which is adequate, the preparation done by the teacher before learning, school regulations which require using the natural environment as a source of learning, enthusiasm and enthusiasm of students in learning, facilities and infrastructures in the use of nature as Learning Resources. Then for the inhibiting factor is the weather that is less supportive, students who are too active difficult to be conditioned, and less optimal use if there are no media or tools and supporting materials.